\(x^2+3x+1=\left(x+3\right)\sqrt{x^2+1}\)
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^2+3x+1=\left(x+3\right)\sqrt{x^2+1}\)
<=> \(2x^2+6x+2-2\left(x+3\right)\sqrt{x^2+1}=0\)
<=> \(\left(x^2+6x+9\right)-2\left(x+3\right)\sqrt{x^2+1}+x^2+1-8=0\)
<=> \(\left(x+3-\sqrt{x^2+1}\right)^2=8\)
<=> \(\orbr{\begin{cases}x+3-\sqrt{x^2+1}=2\sqrt{2}\left(1\right)\\x+3-\sqrt{x^2+1}=-2\sqrt{2}\left(2\right)\end{cases}}\)
(1) <=> \(x+3-2\sqrt{2}=\sqrt{x^2+1}\)
<=> \(\hept{\begin{cases}x\ge2\sqrt{2}-3\\2\left(3-2\sqrt{2}\right)x+\left(3-2\sqrt{2}\right)^2=1\end{cases}\Leftrightarrow}x=2\sqrt{2}\)
(2) <=> \(x+3+2\sqrt{2}=\sqrt{x^2+1}\)
<=> \(\hept{\begin{cases}x\ge-2\sqrt{2}-3\\2\left(3+2\sqrt{2}\right)x+\left(3+2\sqrt{2}\right)^2=1\end{cases}\Leftrightarrow}x=-2\sqrt{2}\)
Vậy phương trình có 2 nghiệm:..